(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Train stations are an important part of modern urban history. Large stations have helped to form the public image of the city in which they are located. Train stations are important distribution areas and exchanges where different types of transport are connected. It is a meeting place for people, commercial, recreational and cultural centers, due to the neglect and deterioration of local stations, especially with regard to the functional aspects in terms of providing the necessary amenities, movement and waiting, and weak in achieving the aspects of sustainability in the design of these stations, which leads to the atrophy of their effectiveness. The importance of research to work on the development of these stations and revitalization to contribute to the performance of its effectiveness in an integrated manner and to meet the needs of different travelers and encourage them to use public transport, Therefore, many studies have been discussed that dealt with the functional aspects of the design of train stations implicitly or majorly, Therefore, many studies have been discussed that dealt with the functional aspects of the design of train stations implicitly or majorly, but these studies were characterized by plurality and inclusiveness in the introduction of design treatments. Thus, the research problem of "the need to find a comprehensive theoretical concept of functional integration requirements in the design of local train stations" The aim of the research is to "develop a comprehensive theoretical conception of the requirements of functional integration in the design of local train stations."